The First Workers of the Ant Camponotus obscuripes Are a Different Allometric Morph with Relatively Long Antennae to Communicate with Other Larger Colony Members - Saori Watanabe; Mamoru Terayama; Ryota Kawauchiya; Natsuki Ogusu; Yusuke Fujita; Syunta Mikami; Yuuka Murakami; Eisuke Hasegawa (Psyche: A Journal of Entomology)
The first workers produced by an ant queen with a claustral founding mode are much smaller than the workers after the second generation and are thus called “nanitics.” These nanitics shoulder the initial fate of the colony and thus may be different morphometric morph from the other workers in mature colony to optimize the survival of their own colony. We report here that, in the ant Camponotus obscuripes Mayr, the allometric rules of the nanitics are different from those of other workers in mature colonies, suggesting that the nanitics constitute an independent caste as with soldiers or queens in other species. In addition, the antennae of the nanitics show the minimum absolute length-difference with the mother queen compared to the other traits measured. This result suggests that this small size difference enables C. obscuripes nanitics to communicate with the other members of the colony. Our results indicate that polymorphic societies affect the growth rules of workers.